2019
DOI: 10.1016/j.ensci.2019.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Stroke onset to needle delay: Where these golden hours are lost? An Egyptian center experience

Abstract: BackgroundThe use of intravenous recombinant tissue plasminogen activator (IV r-tPA) in early acute ischemic stroke (AIS) management faces a lot of difficulties in developing countries due to lessened guideline development with consecutive pre- and intra-hospital delay.ObjectivesThe objective was to identify the barriers facing proper utilization of IV r-tPA for AIS in Tanta University Hospitals.MethodsThe study was conducted on 4124 AIS patients eligible to use IV r-tPA divided to group-I consisting of 442 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
16
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 22 publications
5
16
1
4
Order By: Relevance
“…In a study in Egypt, only 5.8% of those who were eligible for receiving intravenous thrombolysis received intravenous rtPA which is to a large extent lower than our study results. Their study showed that the Mean±SD onset-to-arrival time was 147.2±42.5 min and the Mean±SD DNT was 87.5±16.4 min [18]. In comparison with the current study, they had a better arrival time even though our DNT is much better.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…In a study in Egypt, only 5.8% of those who were eligible for receiving intravenous thrombolysis received intravenous rtPA which is to a large extent lower than our study results. Their study showed that the Mean±SD onset-to-arrival time was 147.2±42.5 min and the Mean±SD DNT was 87.5±16.4 min [18]. In comparison with the current study, they had a better arrival time even though our DNT is much better.…”
Section: Discussioncontrasting
confidence: 67%
“…This result is in line with the work of Wafkin and colleagues who reported that the main causes of prehospital onset-to-arrival delay were stroke unawareness, long travel time, incorrect beliefs, non-available neurologists, stroke onset during sleep. Also, the causes of in-hospital delays include prolonged DNT, financial restraints, minor strokes, unavailable beds, and fear of complications [18].…”
Section: Discussionmentioning
confidence: 99%
“…Kalimantan selatan merupakan provinsi yang luas, sehingga diperlukan transportasi yang baik untuk pasien stroke. Dengan mengingat waktu golden time dalam pengobatan stroke adalah ± 3 jam, yang berarti bahwa dalam 3 jam pertama setelah terindikasi stroke, perawatan lengkap dan optimal harus segera didapat pasien agar usaha pengobatan yang dilakukan berhasil (Bahnasy, Ragab, & Elhassanien, 2019) Penatalaksanaan dan pengobatan yang cepat tidak hanya membuat perbedaan antara hidup dan mati, tetapi juga dapat mengurangi kecacatan jangka panjang dan komplikasi lainnya. Komplikasi neurologis termasuk perkembangan stroke iskemik, transformasi hemoragik simptomatik, stroke berulang sejak onset stroke (Asgedom et al, 2020).…”
Section: Pendahuluanunclassified
“…Pengangkutan pasien yang tepat waktu dan aman dari tempat gawat darurat ke fasilitas perawatan kesehatan yang sesuai untuk perawatan lebih lanjut adalah proses yang kompleks (Tiwary, Nilima, Majumdar, Singh, & Khan, 2020 Berdasarkan tabel 5 menunjukkan waktu tempuh antara lokasi berangkat dengan instalasi gawat darurat RSUD Ratu Zaleha didapatkan hasil 17 informan (56,57%) ≥165 menit. Waktu emas (golden window) dalam penanganan stroke adalah ± 3 jam, artinya dalam 3 jam awal setelah mendapatkan serangan stroke, pasien harus segera mendapatkan terapi secara komprehensif dan optimal dari tim gawat darurat rumah sakit untuk mendapatkan hasil pengobatan yang optimal (Bahnasy et al, 2019). Keterlambatan pra-rumah sakit, yang diukur dengan total waktu transportasi yang melebihi pedoman bisa disebabkan oleh musim (cuaca) dan pusat pelayanan gawat darurat yang tersedia (Golden & Odoi, 2015).…”
Section: Alasan Penggunaan Transportasiunclassified
“…In another study in Egypt, the mean onset-to-arrival time was 147.2 minutes and the mean time between the hospital arrival and rTPA injection was 87 minutes. The main causes of delay in patients were misperception of stroke symptoms and long distances from health centers (22).…”
mentioning
confidence: 99%